Plio/Pleistocene benthic stable isotopes (d18O, d13C) of gravity core SO264_28-2 - Dirk Nürnberg; Nadine Gehre; Sebastian Fessler (PANGAEA, 2025)
Sediment cores from the volcanic Emperor Seamount Chain obtained during RV SONNE cruise SO264 (SONNE-EMPEROR) in August 2018 allow us to reconstruct lateral changes in the subarctic and subtropical gyres in the pelagic North Pacific over the last ~3.4 million years. This dataset comprises benthic stable carbon (δ13C) and oxygen isotope (δ18O) data from gravity core SO264-28-2, which was recovered from Suiko Seamount (44°51.547 N 170°03.997 E) from 1935 m water depth. Measurements were performed on the benthic foraminiferal species Uvigerina peregrina, Cibicidoides wuellerstorfi, and Melonis barleanum. Sampling and analytical studies were carried out from 0.00–7.62 m core depth at ~2 cm spatial resolution. The isotope analyses were performed on a Thermo Scientific MAT 253 mass spectrometer with an automated Kiel IV carbonate preparation device.